The Treatment Outcome of PMX-DHP for the Treatment of SIRS Caused by Perforation the Large Intestine - Mukai, Hirokado; Nakamura, Kisuke; Matsue, Toshihide; Takashima, Shigeki; Nakajima, Kazunori; Saito, Hitoshi; Hayashi, Kei (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2013)
Objectives: The purpose of this study was to retrospectively evaluate the usefulness and limitations of polymyxin B direct hemoperfusion (PMX-DHP) for the treatment of systemic inflammatory response syndrome (SIRS) caused by perforation of the large intestine. Subjects and Methods: The subjects were 64 patients with SIRS due to perforation of the large intestine who had undergone PMX-DHP. Clinical findings and temporal changes in various mediators were evaluated in the survival and deceased groups. Surgical treatment was performed in all patients, and continuous hemodiafiltration (CHDF) was also performed in 12 patients. Results: Fifty-three patients (82.8%) survived, and the treatment results significantly improved after the introduction of PMX-DHP. The APACHE-II and SOFA scores in the deceased group were significantly higher than in the survival group. The periods between the occurrence of this disease and surgery and between surgery and the start of PMX-DHP were significantly shorter in the survival group than in the deceased group. The percentage of patients in whom the dose of dopamine could be reduced was significantly higher in the survival group than in the deceased group. With regard to the relationship between organ failure and prognosis, dysfunction of more than 4 organs was a concomitant complication in all patients of the deceased group. The prognosis was significantly poorer in patients with dysfunction of the liver and the central nervous system. There was no significant difference in the blood endotoxin level between the survival and deceased groups. However, the IL-6 and IL-10 levels were significantly lower in the survival group than in the deceased group, and the rates of changes in these levels were significantly lower in the former. Among the patients who underwent CHDF, only 5 patients (41.7%) survived. Conclusions: PMX-DHP was useful for the treatment of perforation of the large intestine in patients with SIRS symptoms, and early treatment with this method was considered important. Treatment of patients with dysfunction of more than 4 organs or dysfunction of the liver and the central nervous system by this method alone may be insufficient to ensure recovery.